Cost of Treatment Demam Berdarah Dengue (DBD) di Rawat Inap Berdasarkan Clinical Pathway di RS X Jakarta - Rejeki, Vera Marietha Meinar; Nurwahyuni, Atik (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Hospitals as health care providers are now required to perform cost and quality control without neglecting the quality of services. Clinical pathways which underlying quality and cost control in the hospital are available but has not been audited. This study aims to determine the unit cost of services in RS X Jakarta, the utilization of hospital services for dengue disease and cost of treatment of DHF in RS X Jakarta. A cross-sectional study was performed in this study. A quantitative approach was done through data collection from hospital information system, medical record and financial data. The result showed that there was a gap between the cost of treatment of DHF patients which based on the clinical pathway (2,184,588 IDR) and the cost of treatment based on the real condition (2,382,512 IDR). The biggest difference between cost of treatment and real cost was in the hospitalization cost and medicine cost. Cost of treatment without salary and investation calculation for DHF patients can be reduced significantly by 29%. Cost of treatment without salary calculation for DHF patients can be reduced significantly by 42%. There is a need for monitoring system and the establishment of hospital case mix team in order to optimize the hospital clinical pathway in the JKN era.